Relationship between Self-Esteem, Interpersonal Trust, and Social Anxiety of College Students - Xiahong He (Occupational Therapy International)
This study attempts to disclose the relationship between self-esteem, interpersonal trust, and social anxiety of college students and provide an empirical reference for enhancing their self-esteem, cultivating their interpersonal trust, and reducing their social anxiety. Specifically, 673 college students were randomly sampled and measured against the self-esteem scale (SES), interpersonal trust scale (TS), and interaction anxiousness scale (IAS). The results show that self-esteem does not vary significantly with genders and origins; social anxiety does not vary significantly with origins but differs significantly between genders; the social anxiety of males is much lower than that of females; interpersonal trust differs significantly between genders and between origins. Self-esteem is significantly correlated with interpersonal trust (r=0.22, p<0.01). Social anxiety has a significant negative correlation with self-esteem (r=−0.17, p<0.01) and with social anxiety (r=−0.26, p<0.01). Interpersonal trust partly mediates the relationship between self-esteem and social anxiety. These findings provide a theoretical basis for enhancing and improving mental health education of college students.